Rural Profile - Kristin Pullyblank (Rural Nurse Organization; Binghamton University, 2022)
Purpose: It has been well-documented that rural communities experience poorer health outcomes than urban or suburban communities. The contribution of various structural and sociodemographic factors to this disparity has been well studied. However, research on the impact of the rural profile on health outcomes is understudied, in part because what it means to "be rural" has not been well defined nor operationalized.  Methods: Walker and Avant's traditional concept analysis method was used Findings: The rural profile was defined as the set of personal attitudes, beliefs and behaviors that are typically informed by the structural and demographic elements found in less densely populated areas. The attributes of the rural profile are self-reliance, close community and family ties, and an emphasis on place. Observable indicators for each of these attributes based on previously published research are discussed. Conclusions: While conceptualizing the rural profile is challenging, it is imperative to define and operationalize this concept in order to better address the health needs of rural people and communities. Keywords: Concept analysis, rural, health behavior, rural beliefs DOI:  https://doi.org/10.14574/ojrnhc.v22i2.716